DUNIA SOSIAL POLITIK RIIL HEGELIAN: DOMAIN REKONSILIASI KEBAIKAN SUBYEKTIF DAN OBYEKTIF - Ujan, Andre Ata (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2007)
The old polarity between hyper-liberalism and hypercollectivism is in fact still very much alive until now. This article seeks to do justice to both poles by utilizing Hegel's “Philosophy of Mind”. The concept of 'worldconsciousness' is elaborated as Absolute Reason in which individual and society are united without losing themselves, without letting one be swallowed by the other.The ethical life developed by Hegel is a process in which individual comes to find her/himself through the dialectic between subjective and objective good. Society is viewed as an organism by which individual finds her/his dignityas a person.